Urban expansion of the city of Zawiya onto agricultural land.: Urban expansion of the city of Zawiya onto agricultural land. (jornal of the libyan geographical society, 2009)
The problem of shrinking agricultural land as a result of urban expansion is one of the negative effects produced by the phenomenon of urban growth in most cities of the world, both developed and developing, during the twentieth century, especially in the second half of it, and it is no less serious than the rest of the problems associated with this phenomenon. Such as unemployment, housing and transportation crises, lack of services, pollution and social ills.The phenomenon of urban sprawl onto agricultural lands has environmental effects, as well as economic effects. It represents a manifestation of environmental imbalance in that it leads to the shrinking of agricultural land areas surrounding urban centers.  Besides being one of the human causes of desertification, and exacerbating it, urban sprawl onto agricultural land leads to the displacement of agricultural areas at the expense of pastures, which are forced to retreat to impoverished, marginal areas, thus accelerating desertification. The disappearance of thousands of hectares of agricultural land, which is the most valuable and important resource for providing food, also poses a threat to national food security.The harsh natural conditions in Libya have limited the country's potential for agricultural expansion, with the majority of the population residing in the coastal region, specifically in the northwestern and northeastern poles, which represent the best parts of the country for human settlement due to their suitable climate and fertile soil, while the rest of the country appears to be areas of population displacement. Therefore, the phenomenon of urban sprawl encroaching on agricultural land can be described as one of the most sensitive problems resulting from rapid urbanization in Libya, due to the limited amount of agricultural land, which represents only 2% of its total area. The situation is further exacerbated by the fact that this expansion has come at the expense of the most productive agricultural land.This research seeks to monitor the urban expansion of the city of Zawiya at the expense of the surrounding agricultural lands, which are among the most fertile lands, and their transformation into areas covered by concrete buildings designated for housing and other urban services.
Keywords: Shrinking agricultural land; Urban expansion; Urban growth; Urban sprawl; ecological imbalance; Zawiya city